Research on the Early Warning Method of Water Delivery Pipeline Detonation Based on High-frequency Water Pressure Monitoring. Issue 4 (January 2021) - Xinmin, Zhu; Tianxiang, Lin; Shaokong, Feng; Feng, Shang; Zhe, Fan
Abstract: In order to study a novel monitoring method suitable for pressure water conveyance project, the fiber grating pressure sensor was adopted for monitoring the water pressure of in-service glass fiber reinforced plastic mortar pipeline. An emptying valve was used in the prototype test to simulate the leakage process and the dynamic water pressure process was recorded effectively by the fiber grating pressure sensor with high frequency and high precision. According to prototype test results, a fluctuation analytical method was proposed, which uses random average pressure as the equilibrium standard value. Meanwhile, an early warning system against pipe failure was developed based on this method. The system was verified by the simulated leakage tests, and the results show that the system could alarm the leakage of more than 0.25% of pipeline design flow, and the positioning accuracy was 10 m–20 m.